Non-coding RNA in cartilage regeneration: regulatory mechanism and therapeutic strategies - Wen, Mengnan; Guo, Xueqiang; Zhang, Jingdi; Li, Yunian; Li, Jixiang; Fan, Zhenlin; Ren, Wenjie (Frontiers in Bioengineering and Biotechnology, 2025)
The pathogenesis of cartilage injury and degeneration is exceptionally complex. In addition to being associated with osteoarthritis and trauma, factors such as age, gender, obesity, inflammation, and apoptosis of chondrocytes are also considered significant influencing factors. Due to the lack of direct blood supply, lymphatic circulation, and neural innervation, coupled with low metabolic activity, the self-repair capability of cartilage after injury is extremely limited, making its treatment quite challenging. Recent research indicated that ncRNA, a class of RNA transcribed from the genome that does not encode proteins, played a crucial regulatory role in various disease processes. Particularly noteworthy is its positive regulatory role in cartilage regeneration, achieved through the modulation of the inflammatory microenvironment, promotion of chondrocyte proliferation, inhibition of chondrocyte degradation, and facilitation of the recruitment and differentiation of bone marrow mesenchymal stem cells into chondrocytes. In the earlier phase, we conducted a review and outlook on therapeutic strategies for the regeneration of articular cartilage injuries. This article specifically focuses on summarizing the regulatory roles and research advancements of ncRNA in cartilage regeneration, as well as its contributions to the clinical application of gene therapy for cartilage defects.